SOSIALISASI KEPADA MASYARAKAT DESA SELAMAT, KECAMATAN TENGGULUN, KABUPATEN ACEH TAMIANG DALAM PEMANFAATAN SUMBER DAYA AIR SEBAGAI POTENSI PERENCANAAN PEMBANGUNAN PLTMH - Apriana, Winda; Mutia, Eka; Yusri, Azwar (Fakultas Teknik, Universitas Samudra, 2023)
Utilization of renewable energy using water flow as a power generator is one of the easiest solutions to implement. Microhydro Power Plants are small-scale water power plants with an output capacity of less than 100 kW, which are environmentally friendly and relatively inexpensive to maintain. Desa Selamat has five waterfalls and river streams, indicating its potential for utilizing natural resources as microhydro power plants (PLTMH). Socialization activities are conducted to ensure that the community understands PLTMH before construction begins. The methods used include socialization, discussions, and Q&A sessions. Gunung Pandan Waterfall has a height of 11.8 meters, a width of the river below of 7 meters, and a depth of less than 1 meter. The outcome shows that the community and local government are very enthusiastic and receptive to the suggestions and inputs provided.